PEMBELAJARAN IPS BERBASIS KEMAMPUAN BERPIKIR SEBAGAI ALTERNATIF INOVASI PEMBELAJARAN INTERAKTIF - Handini, Oktiana (Widya Wacana: Jurnal Ilmiah, 2016)
Knowledge construction process forces people to chose thinking ability which be able toconnect knowledge content with real life. Social science learning is very complicated. It relateswith otentic and holistic real fenomenon. To realize good social science learning, learningparadigm growth, knowledge contruction undestanding are absolutely needed. Social sciencelearning needs strategies suitable with constructive prespective. It means learners constructthemselves to get many real and holistic knowledges. The skill to process knowledge is thinkingability in metacognitive dimension, critical, creative, thinking process and essencial thinkingprocess so that understanding how to connect knowledge content with real world be inreractiveconcepts. This learning strategy is interactive learning innovation alternative.Keywords : Thinking Ability, interactive learning innovation alternative.